2021
DOI: 10.1111/1460-6984.12651
|View full text |Cite
|
Sign up to set email alerts
|

French speech–language therapy students’ interest in evidence‐based practice: A survey

Abstract: Background: Taking into account international studies interested in the development of evidence-based practice (EBP) in the speech and language therapy field, this survey investigated key issues with regard to students' perception of EBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Les revues professionnelles et scientifiques ont un rôle de plus en plus important dans la diffusion des données de la recherche en orthophonie, ce qui s'explique en particulier par l'adoption croissante du modèle de la « pratique fondée sur les preuves » (evidence-based practice) (Maillart et Durieux 2014 ;Witko et al 2021). Ce modèle encourage en effet les thérapeutes à élaborer leur raisonnement clinique en incorporant les observations cliniques, les préférences du patient, ainsi que les données issues de la littérature spécialisée.…”
Section: A Metadata Analysis Of the French Speech And Language Therap...unclassified
“…Les revues professionnelles et scientifiques ont un rôle de plus en plus important dans la diffusion des données de la recherche en orthophonie, ce qui s'explique en particulier par l'adoption croissante du modèle de la « pratique fondée sur les preuves » (evidence-based practice) (Maillart et Durieux 2014 ;Witko et al 2021). Ce modèle encourage en effet les thérapeutes à élaborer leur raisonnement clinique en incorporant les observations cliniques, les préférences du patient, ainsi que les données issues de la littérature spécialisée.…”
Section: A Metadata Analysis Of the French Speech And Language Therap...unclassified
“…Following the initial work of Moscovici in 1961 [11,12], Abric developed central core theory in 1976 [9]. Amongst the different methods for collecting social representations, the method recommended by Abric [15] is the free association method followed by a posteriori ranking of the cited elements [15,25].…”
Section: Frameworkmentioning
confidence: 99%
“…The issue of the importance of core work has also been raised with regard to nurses [8] who share the same mission as other paramedical professionals, i.e., providing patients with clinical services and care. This importance of core work should be considered alongside the strong interest in evidence-based practices, as one study found that up to 73.6% of speech therapy students felt they were competent in implementing at least some of these practices [9]. The discrepancy between the positive attitudes and involvement in research might be explained by the fact that paramedical professionals do not see research as part of their role or that their training does not enable them to get involved in research.…”
Section: Introductionmentioning
confidence: 99%